2023
DOI: 10.1093/cei/uxad029
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptome analysis reveals endometrial immune microenvironment in minimal/mild endometriosis

Abstract: Endometriosis is a common inflammatory disorder in women of reproductive age due to an abnormal endometrial immune environment and is associated with infertility. This study aimed to systematically understand the endometrial leukocyte types, inflammatory environment, and impaired receptivity at single-cell resolution. We profiled single-cell RNA transcriptomes of 138,057 endometrial cells from endometriosis patients (n=6) and control (n=7), respectively, using 10x Genomics platform. We found that one cluster o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…We started by creating a single-cell reference atlas, which we termed the HECA ( Figure 1c ). To create the HECA, we integrated six publicly available single-cell RNA sequencing (scRNA-seq) datasets (Wang et al 14 , Garcia-Alonso et al 15 , Tan et al 16 , Lai et al 19 , Fonseca et al 17 , Huang et al 18 ) with our newly generated dataset (termed Mareckova (cells) dataset) ( Figure 1b ). Harmonisation of metadata across the studies and application of strict data quality control filters ( see Methods ) was essential for the integration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We started by creating a single-cell reference atlas, which we termed the HECA ( Figure 1c ). To create the HECA, we integrated six publicly available single-cell RNA sequencing (scRNA-seq) datasets (Wang et al 14 , Garcia-Alonso et al 15 , Tan et al 16 , Lai et al 19 , Fonseca et al 17 , Huang et al 18 ) with our newly generated dataset (termed Mareckova (cells) dataset) ( Figure 1b ). Harmonisation of metadata across the studies and application of strict data quality control filters ( see Methods ) was essential for the integration.…”
Section: Resultsmentioning
confidence: 99%
“…the eutopic endometrium) differs between those with and without endometriosis 26,27 . Recently, single-cell studies analysing small sample sizes, reported dysregulation of the stromal and immune compartments in the endometrium of women with endometriosis to various degrees 16,18,20,28,29 . Larger sample sets are now needed if we are to unpick whether and how the endometrium differs in those with and without the condition.…”
Section: Mainmentioning
confidence: 99%
“…Menstrual endometrium scRNAseq in endometriosis patients reveals decreased decidualization markers in stromal fibroblasts, reduced frequencies of uNK cells, and enrichment of B cells, demonstrating that menstrual endometrium reflects secretory endometrium abnormalities as possible biomarkers of disease 89 . Another study on mid‐secretory endometrium (i.e., the window of implantation, (WOI)) of stage I/II subjects revealed that in one epithelial cell cluster PAEP and CXCL14 expression was absent, immune cells had higher pro‐inflammatory cytokine expression, and no cycle variation of uNK and T cell frequencies was observed versus controls 91 . Lower epithelial receptivity markers, abnormal immune cell frequencies, and a pro‐inflammatory WOI likely adversely affect implantation and pregnancy outcomes in patients with stage I/II disease.…”
Section: Methodsmentioning
confidence: 99%
“…[84][85][86][87] These studies underscore heterogeneity of specific cell types and altered features in different hormonal states across the menstrual cycle and provide a key backdrop to studies on endometrium and endometriosis lesions at the single-cell level. Recently, scRNAseq [88][89][90][91][92] have complemented bulk tissue, blood, peritoneal fluid, and in vitro cellular and tissue organoid analyses of endometriosis lesions and endometrium from cases versus controls without disease (Table 2). These have provided further insights into the heterogeneity of cell types/subtypes, unique clusters, and signatures informing mechanisms and pathways involved in cellular dysfunctions relevant to pain and fertility compromise in patients with disease.…”
Section: Single-cell Rnaseqmentioning
confidence: 99%
See 1 more Smart Citation